2014
DOI: 10.1161/circoutcomes.114.001230
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Trial of a Virtual Cardiac Rehabilitation Program Delivered at a Distance via the Internet

Abstract: With an aging population in many Western countries and increases in risk factors such as obesity, the number of patients with cardiovascular diseases (CVDs) is increasing. 1 These patients are at greater risk of subsequent events, comorbidities, and premature mortality, therefore effective and ongoing management is needed to reduce this risk. Cardiac rehabilitation programs (CRPs) are effective at improving lifestyle behaviors and reducing risk factors in patients with CVD, as well as reducing CVD events and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
165
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(167 citation statements)
references
References 39 publications
1
165
0
1
Order By: Relevance
“…Two RCTs testing Web-based interventions in ACS patients measured an objective physical activity outcome (steps per day or exercise capacity) and reported serious adverse cardiac or mortality events requiring hospitalization per treatment group [28,29]. Reid et al reported four hospitalisations for chest pain and no deaths in the experimental group, and six hospitalisations for chest pain, one for cardiac surgery and two deaths in the control group during 12 months of follow-up [28] Lear et al reported three (9%) major cardiac events (e.g., revascularisation, stroke, and death) in the experimental group, and six (16%) in the control group during 16 months of follow-up [29]. These data suggest that fewer serious adverse cardiac or mortality events are found in favor of Web-based experimental groups, and too few events occur to plan mortality as a primary or secondary outcome within a feasible timeframe.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Two RCTs testing Web-based interventions in ACS patients measured an objective physical activity outcome (steps per day or exercise capacity) and reported serious adverse cardiac or mortality events requiring hospitalization per treatment group [28,29]. Reid et al reported four hospitalisations for chest pain and no deaths in the experimental group, and six hospitalisations for chest pain, one for cardiac surgery and two deaths in the control group during 12 months of follow-up [28] Lear et al reported three (9%) major cardiac events (e.g., revascularisation, stroke, and death) in the experimental group, and six (16%) in the control group during 16 months of follow-up [29]. These data suggest that fewer serious adverse cardiac or mortality events are found in favor of Web-based experimental groups, and too few events occur to plan mortality as a primary or secondary outcome within a feasible timeframe.…”
Section: Discussionmentioning
confidence: 99%
“…The other two RCTs tested nontailored interventions measuring the primary outcome of exercise capacity compared with usual care [29,30]. One RCT found a significantly greater increase in a proxy outcome of exercise capacity, maximal time on treadmill, in favor of the experimental group [29].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, Web-based delivery of a virtual cardiac rehabilitation program was safe and effective for CVD risk reduction. 172 Similarly, mobile messaging was associated with greater physical activity and weight loss. 173 These early successes have prompted the ongoing development of other mobile applications to improve health-related behaviors such as smoking cessation and medication adherence.…”
Section: Patient-reported Informationmentioning
confidence: 98%